Identification of a novel TSC2 c.3610G > A, p.G1204R mutation contribute to aberrant splicing in a patient with classical tuberous sclerosis complex: a case report - Ruixiao Zhang; Jianhong Wang; Qing Wang; Yue Han; Xuejun Liu; Irene Bottillo; Yanhua Lang; Leping Shao (BMC, 2018)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterized by hamartomas in any organ systems. Mutations in the TSC1 or TSC2 gene lead to the dysfunction of hamartin or tuberin proteins, which cause tuberous sclerosis complex. Case presentation We describe the clinical characteristics of patients from a Chinese family with tuberous sclerosis complex and analyze the functional consequences of their causal genetic mutations. A novel heterozygous mutation (c.3610G > A) at the last nucleotide of exon 29 in TSC2 was identified. On the protein level, this variant was presumed to be a missense mutation (p.Gly1204Arg). However, the splicing assay revealed that this mutation also leads to the whole TSC2 exon 29 skipping, besides the wild-type transcript. The mutated transcript results in an in-frame deletion of 71 amino acids (p.Gly1133_Thr1203del) and its ratio with the normal splice product is of about 44:56. Conclusions The novel c.3610G > A TSC2 mutation was identified in association with tuberous sclerosis complex. And it was proven to code both for a missense-carrying transcript (56%), and for an isoform lacking exon 29 (44%).